Endovascular therapy in patients with large vessel occlusion due to cardioembolism versus large-artery atherosclerosis. (March 2021) - Zotter, Meredeth; Piechowiak, Eike I.; Balasubramaniam, Rupashani; Von Martial, Rascha; Genceviciute, Kotryna; Blanquet, Marisa; Slavova, Nedelina; Sarikaya, Hakan; Arnold, Marcel; Gralla, Jan; Jung, Simon; Fischer, Urs; et al.
Background and aims: To investigate whether stroke aetiology affects outcome in patients with acute ischaemic stroke who undergo endovascular therapy. Methods: We retrospectively analysed patients from the Bernese Stroke Centre Registry (January 2010–September 2018), with acute large vessel occlusion in the anterior circulation due to cardioembolism or large-artery atherosclerosis, treated with endovascular therapy (±intravenous thrombolysis). Results: The study included 850 patients (median age 77.4 years, 49.3% female, 80.1% with cardioembolism). Compared with those with large-artery atherosclerosis, patients with cardioembolism were older, more often female, and more likely to have a history of hypercholesterolaemia, atrial fibrillation, current smoking (each p < 0.0001) and higher median National Institutes of Health Stroke Scale (NIHSS) scores on admission ( p = 0.030). They were more frequently treated with stent retrievers ( p = 0.007), but the median number of stent retriever attempts was lower ( p = 0.016) and fewer had permanent stent placements ( p ⩽ 0.004). Univariable analysis showed that patients with cardioembolism had worse 3-month survival [72.7% versus 84%, odds ratio (OR) = 0.51; p = 0.004] and modified Rankin scale (mRS) score shift ( p = 0.043) and higher rates of post-interventional heart failure (33.5% versus 18.5%, OR = 2.22; p < 0.0001), but better modified thrombolysis in cerebral infarction (mTICI) score shift ( p = 0.025). Excellent (mRS = 0–1) 3-month outcome, successful reperfusion (mTICI = 2b–3), symptomatic intracranial haemorrhage and Updated Charlson Comorbidity Index were similar between groups. Propensity-matched analysis found no statistically significant difference in outcome between stroke aetiology groups. Stroke aetiology was not an independent predictor of favourable mRS score shift, but lower admission NIHSS score, younger age and independence pre-stroke were (each p < 0.0001). Stroke aetiology was not an independent predictor of heart failure, but older age, admission antithrombotics and dependence pre-stroke were (each ⩽0.027). Stroke aetiology was not an independent predictor of favourable mTICI score shift, but application of stent retriever and no permanent intracranial stent placement were (each ⩽0.044). Conclusion: We suggest prospective studies to further elucidate differences in reperfusion and outcome between patients with cardioembolism and large-artery atherosclerosis.